Royale Pet's - Aslih, Mohd Shahrazi; Gahzali, Nur Zaffan; Ag Rahim, Dayang Nurfaerra; Wahid, Nurul Wahidah; Abd Gani, Nor Firdhaus; Selamat, Nisazirah (2015)
Our business is owned actively by partnership, incorporated as Royale Pet's which is chosen after an agreement made by all partners. This company was introduced by Mr Mohd Shahrazi, who is also the general manager of this company. This company provides a service that cover everything medically and veterinary expenses for your pet. Royale Pets' is providing a medical card for our customers' pet which our customer can use for their pets whenever there is cases such as medical emergency, trauma, disease and so forth. Our company's medical card will allow our customer to have service such as annual examination, consultation, and vaccination or other tests and treatments in certain clinic that we linked. Our company is the first company who has this service in Sabah. This business has good future prospects. It is because it has highly demand because we are preparing new and unique services and it differs from others services. In addition, we are also planning to expand our wings by opening several branches around Peninsular Malaysia.